Modeling the impact of macroenvironmental forces on investment in Renewable Energy Technologies in Ghana: the moderating role of Entrepreneurship orientation dimensions - Michael Karikari Appiah; Rosemary Anderson Akolaa; Angela Kyerewaa Ayisi-Addo (Cogent Economics & Finance, 2022)
Since 2011, successive Governments in Ghana have developed, and implemented Renewable Energy Master Plan to leverage macroenvironmental forces and encourage indigenous investment in Renewable Energy Technologies (RETs), but the actual impacts are yet to be felt by Ghanaians. The main objectives of the study are to: examine the impacts of Macroenvironment Forces (MF) on Small and Medium Enterprises' (SMEs) investment intentions in RETs, and determine the moderating effects of Entrepreneurship Orientation (EO) dimensions (viz. proactiveness, competitive aggression, innovativeness, and risk-taken) on the relationship between MF and SMEs' investment intentions. A total of 240 usable responses were received through self-administered survey questionnaires among Ghanaian SMEs. Variance-Based Partial Least Square Equation Modelling (PLS-SEM) approach was used for the data analyses and hypotheses testing. The results revealed that MF had significant and positive relationship with SMEs' intention to invest in RETs. Moreover, the results showed that proactiveness, competitive aggressive, and innovation had direct effects on intention to invest in RETs. Again, the results showed that EO dimensions significantly moderated the relationship between MF and investment intentions in RETs. The implications of these results include extending previous MF works by evaluating MF, EO, and investment intention relationships in a developing country context, which has been largely ignored in previous studies. Again, this paper provides insights into the value of macroenvironment scanning and assessment which could lead to better investment intentions in clean, affordable, and reliable energy service. Besides, the efficacy of EO in MF-investment intentions relationship has been well established in this paper.
Keywords: 330; Macroenvironment Forces; Entrepreneurship Orientation; SMEs' Investment; Renewable Energy Technologies; Structural Equation Modelling